2006
DOI: 10.1063/1.2355462
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic origin of ferromagnetism in ZnO and Zn0.9Co0.1O magnetic semiconductor films prepared by sol-gel technique

Abstract: We report on the origin of ferromagnetism in ZnO and Co-doped ZnO magnetic semiconductor films prepared by sol-gel technique on Si(100) and SiO2 substrates. X-ray diffraction measurements have shown that ZnO and Co-doped ZnO have the expected wurtzite structure and a preferential orientation along the c axis. Optical transmittance measurements revealed that Co is incorporated into the lattice, as Co2+ substituting Zn2+ ions. Magnetization measurements have shown room-temperature ferromagnetism for both ZnO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 29 publications
1
54
0
1
Order By: Relevance
“…Presently, there is no consensus on the exact exchange mechanism in such WBG-DMSs [6]. The ferromagnetism in ZnO has been attributed to defect-induced [7] or defect-mediated magnetism [8][9][10][11][12]. Furthermore, a density functional theory (DFT) study of Eu-doped ZnO reported ferromagnetic coupling when the RE atoms were in nearest neighbor positions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, there is no consensus on the exact exchange mechanism in such WBG-DMSs [6]. The ferromagnetism in ZnO has been attributed to defect-induced [7] or defect-mediated magnetism [8][9][10][11][12]. Furthermore, a density functional theory (DFT) study of Eu-doped ZnO reported ferromagnetic coupling when the RE atoms were in nearest neighbor positions [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inconsistent experimental results raise a new problem of explaining the mechanism of ferromagnetism in TM-doped ZnO. Moreover, it is difficult to exclude the possibility that the ferromagnetism might be brought by a secondary phase of TM oxides or TM dopant clusters [13,14,15]. Consequently, many researchers turned their attention to non-TM doped ZnO and tried to provide undisputed intrinsic DMS.…”
mentioning
confidence: 99%
“…Note that SQUID magnetometry is an integral method, which measures the total magnetic response from the sample, including substrate and possible contaminations from previous processing [43,44]. On the other hand, conversion electron Mössbauer spectroscopy (CEMS) is an element specific method, which was used to investigate the 57 Fe lattice sites, electronic configuration and corresponding magnetic hyperfine fields.…”
Section: Experimental Methodsmentioning
confidence: 99%